The firm as an entity before the Companies Acts - Getzler, JS; Macnair, M (Four Courts Press, 2005)
In this paper we suggest a counter-narrative to the orthodox picture of the development of company form in England. Company law textbooks tell a story of gradual development, first of forms of partnership trading, then of chartered companies and trading trusts, then ad hoc joint stock companies through private legislation, and finally general incorporation mandated by public legislation. The Bubble Act interrupts this teleology but general corporate form emerges by the midnineteenth century victorious. Our general thesis is that without the benefit of formalized organizational law the courts (with some help from legislative enactments) were able to construct a veil between investors and traders affording much of the benefit of the limited liability policy of later law. It was the Court of Chancery that led the way here, through fraud-based doctrines for reversing or presuming conveyances in order to protect creditors, and as an outgrowth of the body of doctrine, its regime for partnership insolvency. In other words, the basic concepts of contract, property and debt priorities could result in a workable organizational law - without formal corporate entities created by the state. General incorporation thus post-dates the classical periods of industrial and commercial revolution, and hence cannot so easily be identified as the rational business form for developed capitalism. This may have implications not only for historical and legal understanding of capitalism, but for policy prescriptions in both the developed and developing economies of today's world.